Perturbations in Conduction in Liquids by Plasma Generated by a Pulsed Laser - Bertuccelli, Daniela (2016)
The objective of this work is to present the results of measuring the changes in temperature, T, oxidation/reduction potential, ORP, normal electrode potential, NEP, and pH of conducting aqueous mixtures in cells in three situations: with two Copper electrodes, with only one electrode and with none. The situation of two conductors is treated with an external potential and with no applied potential. In all these situations, two identically constructed cells were used. One of them was irradiated with a pulsed high-power laser to produce a plasma. The other cell was not irradiated. Our results are thus presented as difference of the two situations. The results confirm that the plasma produces an increase in the production rate of H. It was also obtained some information on the differential precipitation of Cu into the solution. The yield of Cu dilution and the evolution of the other mentioned parameters confirm previous results and is an indirect proof of an increase of H production.